2013
DOI: 10.1007/s00436-013-3657-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Echinococcus multilocularis in red foxes in Poland—current results (2009–2013)

Abstract: The aim of the study was to determine the prevalence of Echinococcus multilocularis in red foxes (Vulpes vulpes) in Poland. Overall, 1,546 intestinal samples from 15 of the 16 provinces in Poland were examined by the sedimentation and counting technique (SCT). The mean prevalence of E. multilocularis in Poland was 16.5 % and was found in 14 of the 15 examined provinces. The mean intensity of infection was 2,807 tapeworms per intestine. Distinct differences in prevalence were observed between regions. In some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 25 publications
5
51
1
Order By: Relevance
“…The distinct differences in parasite prevalence among the examined provinces confirmed the results of our previous investigation in Poland (10). This study showed an apparent division of Poland into two zones: "eastern half" with high prevalence of E. multilocularis, and "western half" with low prevalence of the parasite.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The distinct differences in parasite prevalence among the examined provinces confirmed the results of our previous investigation in Poland (10). This study showed an apparent division of Poland into two zones: "eastern half" with high prevalence of E. multilocularis, and "western half" with low prevalence of the parasite.…”
Section: Discussionsupporting
confidence: 89%
“…However, a slight but statistically significant increase in the prevalence was observed in Opolskie Province. E. multilocularis was not detected in this province in 2010 (10), but in the current study (2014) about 4% of infected foxes were found. In this province, like in the rest of the "western half" of Poland, the sudden increase in E. multilocularis prevalence in foxes did not occur after the anti-rabies campaign at the turn of the 21 st century.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations